Iceland : Fourth Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Iceland's Fourth Post-Program Monitoring Discussions. Iceland's economy has grown strongly on the back of booming tourism. Real GDP grew 3.3 percent in 2013, despite a drop in investment spending. Net exports were the primary driver. High frequency indicators suggest strong net exports-including steady growth in off-season tourism-have continued in Q1 2014, along with rising private consumption. Inflation has fallen below the Central Bank of Iceland's 2.5 percent target but long-term inflation expectations remain noticeably above this level. The government's medium-term fiscal objectives deserve support, but further effort is needed to achieve them.